Trend of disability adjusted life years in people with lung cancer in Florianópolis in the period 2008 to 2012 (Research, Society and Development, 2022)
Introduction: Disability-adjusted life year (DALY), as known as burden of disease, measure the impact of a disease on the population. Lung cancer is one of the leading causes of burden in the world. Objective: To analyze the time trend of disability-adjusted life year in people diagnosed with lung cancer in Florianópolis from 2008 to 2012. Methods: An ecological time series study was performed with data from the Brazilian Mortality Information System to estimate the Years of Life Lost (YLL) and of the Population-Based Cancer Registry (RCBP) for Years of Disability (YLD) to lung cancer in the city. The sum of these generated DALY. Standardized rates, by gender and age group, were estimated. The program Joinpoint was used to indicat the trends. Results: It was estimated 8,791.17 DALYs and 98.2% related to YLL. The indicators showed stability during the time. Males accounted for 58.1% of the burden. Conclusion: The trend of lung cancer burden was stable. However, in the age groups of 50 to 69 years, they represent higher rates. This reinforces the importance of smoking reduction in the population of Florianópolis, in order to reduce the estimated burden.